COVID-19 adenovirus vector vaccine induces higher interferon and pro-inflammatory responses than mRNA vaccines in human PBMCs, macrophages and moDCs - Jiang Miao; Väisänen Elina; Kolehmainen Pekka; Huttunen Moona; Ylä-Herttuala Seppo; Meri Seppo; Österlund Pamela; Julkunen Ilkka (Elsevier, 2025)
Background: During the COVID-19 pandemic multiple vaccines were rapidly developed and widely used throughout the world. At present there is very little information on COVID-19 vaccine interactions with primary human immune cells such as peripheral blood mononuclear cells (PBMCs), monocyte-derived macrophages and dendritic cells (moDCs).
Methods: Human PBMCs, macrophages and moDCs were stimulated with different COVID-19 vaccines, and the expression of interferon (IFN-λ1, IFN-α1), pro-inflammatory (IL-1β, IL-6, IL-8, IL-18, CXCL-4, CXCL-10, TNF-α) and Th1-type cytokine mRNAs (IL-2, IFN-γ) were analyzed by qPCR. In addition, the expression of vaccine induced spike (S) protein and antiviral molecules were studied in primary immune cells and in A549 lung epithelial cells.
Results: Adenovirus vector (Ad-vector) vaccine AZD1222 induced high levels of IFN-λ1, IFN-α1, CXCL-10, IL-6, and TNF-α mRNAs in PBMCs at early time points of stimulation while the expression of IFN-γ and IL-2 mRNA took place at later times. AZD1222 also induced IFN-λ1, CXCL-10 and IL-6 mRNA expression in monocyte-derived macrophages and DCs in a dose-dependent fashion. AZD1222 also activated the phosphorylation of IRF3 and induced MxA expression. BNT162b2 and mRNA-1273 mRNA vaccines failed to induce or induced very weak cytokine gene expression in all cell models. None of the vaccines enhanced the expression of CXCL-4. AZD1222 and mRNA-1273 vaccines induced high expression of S protein in all studied cells.
Conclusions: Ad-vector vaccine induces higher IFN and pro-inflammatory responses than the mRNA vaccines in human immune cells. This data shows that AZD1222 readily activates IFN and pro-inflammatory cytokine gene expression in PBMCs, macrophages and DCs, but fails to further enhance CXCL-4 mRNA expression.